Anatomic and hemodynamic characterization of vertebral artery duplication via color doppler ultrasonography - Xue Han; Wenbo Duan; Wanling Wen; Tian Lin; Dongxu Lu; Juan Du; Li Liu (PLoS ONE, 2025)
Background and objectives Vertebral artery (VA) duplication is an infrequent vascular variation with a dearth of information on hemodynamic parameters. In this study, color Doppler ultrasonography was utilized to evaluate the origins and hemodynamic features of VA duplication to offer a solid reference for clinicians who are endeavoring to gain insights into this particular form of vascular anomaly. Methods A retrospective analysis was conducted on patients with VA duplication detected by color Doppler ultrasonography. The analysis focused on the origins, the transverse course, diameter and the peak systolic velocity (PSV) of each segment of the duplicated VA. Results In the 36 branches in 18 subjecte identified as VA duplication, 27 branches originated from the subclavian artery and 9 branches originated from the aortic arch. The incidence of variation in the non-C6 entry of the medial branch was 94.4%. Significant differences (P < 0.01) were found in the diameter between the lateral and medial branches, as well as between the medial branch and the convergent VA. Moreover, significant differences in PSV were noted between the medial and lateral branches (P = 0.035) and between the medial branch and the convergent VA (P = 0.015). Conclusions VA duplication is correlated with substantial alterations in both the origin and the entry level into the transverse foramen. In our case series of VA duplication, the diameter and PSV of the medial branch is different from that of the convergent VA or the lateral branch, which might be useful for neuro-interventionalists and neck surgeons.